Vaccine hesitancy, state bias, and Covid-19: Evidence from a survey experiment using Phase-3 results announcement by BioNTech and Pfizer. (August 2021) - Kobayashi, Yoshiharu; Howell, Christopher; Heinrich, Tobias
Abstract: Background: Past survey studies document that people strongly prefer Covid-19 vaccines developed domestically over those developed abroad. Available evidence suggests that this preference for domestic vaccines over foreign ones may stem from prejudice against foreign countries, but identifying prejudice-based vaccine preferences is difficult because people also draw inferences about the quality of vaccines based on country of origin. We exploit a unique opportunity provided by the announcement of a viable vaccine by a bi-national venture, BioNTech and Pfizer, to examine the effect of such prejudice on vaccination intentions while controlling for beliefs about the vaccine quality. Methods: We implemented a survey experiment in Germany and the United States (n = 582, 661 respectively) a few days after the BioNTech/Pfizer announcement of a viable vaccine. We randomized the identified company (and country) responsible for the vaccine development between BioNTech (Germany) and Pfizer (U.S.) and asked respondents when they would take said vaccine. Results: In either the German and U.S. samples, we find little evidence that a country of origin of the vaccine makes a difference in when respondents intend to get vaccinated. We also see no evidence that those with a general animus toward the other foreign country would be more biased against a foreign vaccine. Conclusion: Our findings suggest that prejudice against foreign countries may be less of a concern for vaccine hesitancy and that its effect may be highly context specific. Highlights: We study the effect of prejudice against foreign countries on vaccine preferences. We exploit the Phase-3 results announcement of the BioNTech/Pfizer vaccine. Framing the vaccine as domestic or foreign matters little to vaccine preferences. Results are not driven by vaccine refusers or lack of prejudice or Covid-19 fear.